Fear of Covid-19 and Intentions towards Adopting E-Health Services: Exploring the Technology Acceptance Model in the Scenario of Pandemic - Elahi, Muhammad Zubair; Liang, Gao; Malik, Muhammad Jawad; Dilawar, Sana; Ilyas, Bena (International Journal of Business, Economics and Management, 2021)
The aim of this paper was to investigate the link between fear of Covid-19 and individuals’ behavioral intentions toward adopting e-health services by expanding the technology acceptance model (TAM) to incorporate fear of the Covid-19 factor. To empirically testing our proposed theoretical model, we conducted a research survey in Pakistan and collected data from 624 individuals utilizing a non-probability convenience sampling strategy. The outcomes of our study declare that fear of Covid-19 are positively associated with individuals’ attitude and their subsequent behavioral intentions towards adopting e-health services. Perceived ease of use and perceived usefulness of e-health services mediated the relationship between fear of Covid-19 and individuals’ attitude towards adopting e-health services. This research is highly significant in the current scenario of Covid-19. Our study offers a theoretical model to understand why and how fear of Covid-19 is related to an individual’s intentions for adopting e-health services. Moreover, this study also extends the literature of the technology acceptance model TAM by pinpoint the impact of fear of Covid-19.